Reducing Trade Costs in East Africa : Deep Regional Integration and Multilateral Action - Balistreri, Edward J.; Tarr, David G.; Yonezawa, Hidemichi (World Bank Group, Washington, DC, 2014)
There is substantial evidence that with the progressive global decline in tariffs over several decades, trade costs are a more significant barrier to trade than tariffs, especially in Sub-Saharan Africa. This paper decomposes trade costs into three categories: costs that can be lowered by trade facilitation, nontariff barriers, and the costs of business services. The paper develops a 10-region, 18-sector, global trade model that includes Kenya, Tanzania, Uganda, and Rwanda of the East African Customs Union. The analysis finds that deep integration in the East African Customs Union that lowers these trade costs results in significant gains for the four countries, especially from improved trade facilitation. Extending the lowering of nontariff barriers and services liberalization multilaterally would increase the gains between two and seven times, depending on the country. that the analysis also finds that reducing nondiscriminatory services barriers in Kenya and Tanzania would increase welfare even more than multilateral reduction of discriminatory services barriers. The paper is innovative both conceptually and empirically. It contains foreign direct investment in services and is the first paper to numerically assess liberalization of barriers against domestic and multinational service providers in a multi-sector, multi-region, applied general equilibrium model. The paper uses new databases of the ad valorem equivalents of barriers in services and the time in trade costs. Both databases are shown to be important to the results.